Physiological highlights of manganese toxicity symptoms in soybean plants: Mn toxicity responses - Santos, Elcio Ferreira; Kondo Santini, José Mateus [UNESP]; Paixão, Amanda Pereira [UNESP]; Júnior, Enes Furlani [UNESP]; Lavres, José; Campos, Marcelo [UNESP]; Reis, André Rodrigues dos [UNESP] (My University, 2017)
Manganese (Mn) is an essential element for plants; however, high concentrations in certain soil conditions can cause toxicity symptoms in the plant tissue. Here, we describe Mn toxicity symptoms and Mn toxicity responses in soybean plants. Soybean plants exposed to excess Mn showed reductions in the CO2 assimilation rate and stomatal conductance, which in turn resulted in decreased shoot biomass. Furthermore, peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) activity were higher in plants grown with the highest Mn concentration. The Mn doses increased the activity of antioxidant enzymes such as CAT, POD, and SOD. The toxicity symptoms presented by the leaves included hypertrophying of the adaxial epidermis and the formation of necrotic areas with purple-colored veins. Dramatic movement of calcium from the healthy region to the purple-colored necrotic region was observed, as was the exit of potassium from the necrotic area to the healthy region of the tissue. The high activities of POD and SOD in the presence of high Mn compartmented in the roots was the main physiological responses at high Mn uptake by soybean plants.
Keywords: Antioxidative stress; Energy-dispersive X-ray spectroscopy; Gas exchange parameters; Manganese phytotoxicity; Mineral plant nutrition